EFFECTIVENESS OF GOVERNMENT REGULATIONS (PP) NUMBER 43 YEAR 2014 Article 154 paragraph (1) (Study of Sukorejo District, Pasuruan Regency) - Natsir, Mohammad (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
Government Regulation No. 43/2014, Article 154, Paragraph 1, stipulates that the sub-district head, as a part of the regional apparatus, has the task of guiding and supervising the financial management of the village. The performance of the sub-district head is very important because it can bring a village into an optimal government system. Based on the Pasuruan Regent Regulation on the Delegation of Regent Authority to the Camat. The role of the camat is to facilitate, advise, recommend and evaluate the financial management of the village. This cannot be delegated to anyone to avoid misuse of the village budget. This research uses a qualitative and normative approach. Data collection methods through field studies by conducting interviews, documentation and observation as well as looking at literature studies and government regulations to Pasuruan City District officials. The results showed that the sub-district head in carrying out his role as supervisor and supervisor was mostly represented by staff in charge of village finances, so that the village government was dissatisfied because the staff in charge of village finances was considered less competent. Regarding the indicators used in this study related to supervision and guidance in its application, it is still ineffective, so the community is often hindered in making arrangements. In this case, it is expected that the Sub-District Chief will be able to raise awareness and exercise his authority in accordance with the applicable regulations to reduce complaints from the village community.